A argumentação nos livros didáticos de língua portuguesa sob a perspectiva da teoria polifônica da enunciação - Araújo, Letícia Carvalho (2023)
Argumentation is a discursive activity with the potential to promote the learning of reflective reasoning. It can also be understood as a social practice of language, considering that it can be associated with the perspectives, values, beliefs, and ideologies of those who participate in an argumentative interaction in each communicative situation. Therefore, argumentation is part of the set of human actions that require a stance, along with reasonable justification based on acceptable resources to be presented to the interlocutors. In this research, the investigation focuses on the contributions of argumentation within language in the analysis of activities from two textbooks Língua Portuguesa: Linguagem e interação [Portuguese Language: Language and Interaction] and Se liga na língua [Beware of Language]. The aim is to verify how the linguistic- discursiveresources that materialize polyphony are approached. This proposal is in line with the official documents for basic education (OCEM, PCN, BNCC), which guide teachers in their pedagogical work to help students develop abilities to critically evaluate texts and sentences in circulation in society. The underlying conception here is that the analysis ofthe linguistic-discursive elements helps to identify the constitutive marks of positioning and counterarguments in several argumentative situations inside and outside the classroom. In this way, Ducrot's perspectives on argumentation in language were selected as references to help analyze the treatment given by the author to some linguistic resources, especially those that can mitigate or mark a position and forward an idea to its conclusion, such as has been deepened in the studies of TAL. It was also observed how the teaching of argumentation has (or has not) favored this type of work proposed in two textbooks used by schools in Sergipe. The results indicate that the linguistic elements are partially explored in the didactic exercises, although the authors recognize the importance of formulating partly subjective utterances, with marks of adherence or distancing from those who enunciated them when the argumentation is mobilized.